PENERAPAN PENDEKATAN SAVI (SOMATIS, AUDITORI, VISUAL, DAN INTELEKTUAL) PADA MATERI KEANEKARAGAMAN HAYATI DI SMA - Wendraningrum, Dhenok; Tri Martuti, Nana Kariada; Marianti, Aditya (Journal of Biology Education, 2014)
The using approaches , methods , and models of learning that monotonous can cause less motivated students. The purpose of the research is for analizing the effectivity of the SAVI approach toward activity and result of students of SMA Negeri 1 Sragi on biodiversity material . The experiment held in SMA Negeri 1 Sragi Pekalongan second semester in the academic year of 2012/2013. Population of research is a SMA Negeri 1 Sragi students. The sample in this research was taken by purpose sampling. The research design using pre - experimental design approach that is One-Shot Case Study. Result of the research shown thatÂ  activity of students is 90% reached active and very active criteria. Result of completeness of study by student reach â¥ 75. Base on the result of research, we can conclude that SAVI approach is effective if it used in biodiversity material in senior high school. Â Penggunaan pendekatan, metode, dan model pembelajaran yang monoton dapat mengakibatkan siswa kurang termotivasi. Penelitian ini bertujuan menganalisis efektivitas pendekatan SAVI terhadap aktivitas dan hasil belajar siswa SMA pada materi keanekaragaman hayati. Penelitian dilaksanakan di SMA Negeri 1 Sragi Pekalongan semester genap tahun ajaran 2012/2013. Populasi penelitian adalah siswa SMA Negeri 1 Sragi. Sampel dalam penelitian ini diambil dengan purposive sampling. Rancangan penelitian menggunakan pendekatan pre-experimental design yaitu One-Shot Case Study. Hasil penelitian menunjukkan bahwa aktivitas siswa sebesar 90% mencapai kriteria aktif dan sangat aktif. Hasil ketuntasan belajar siswa mencapai nilai â¥ 75. Berdasarkan hasil penelitian dapat disimpulkan bahwa pendekatan SAVI efektif diterapkan pada materi keanekaragaman hayati di SMA.